Outcome of a modified sympathicotomy for cardiac neuromodulation of untreatable ventricular tachycardia. (24th May 2021) - Cauti, FM; Rossi, P; Vannucci, J; Polselli, M; Rossi, C; Iaia, L; Mantovani, S; Bruno, K; Pugliese, F; Quaglione, R; Venuta, F; Bianchi, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OBJECTIVES This study aimed to describe the results of a modified sympathicotomy (uniportal VATs with stellate ganglion sparing) for cardiac sympathetic denervation (CSD) in the setting of untreatable ventricular tachycardia. BACKGROUND. CSD, in patients with refractory ventricular tachycardia (VT), is comprehensively recognized as an important treatment option for patients with structural heart disease as well as congenital inherited arrhythmia syndrome. A recent case series demostrated  the feasibility of the modified technique. METHODS We consecutively enrolled 8 patients with refractory VT. Baseline demographic, medical, and surgical data as well as arrhythmia outcomes and procedural complications were evaluated. RESULTS A total of 8 patients ( 7 pts NIDCM, 1 pt IDCM with mean age:68+-8 years) were enrolled for the treatment of refractory VT with a modified CSD technique. Mean sympathicotomy length were 7.3 (SD 3) min per side. 3/8 patients underwent monolateral (LCSD) sympathicotomy due to strong adesion in the right pleural cavity. Mean follow up was 13 months (SD 6). No complication occurred during the sympathicotomy. An overall reduction in VT burden and VT number was observed after the CSD despite an in-hospital early recurrence in 3 patients. CONCLUSIONS A modified CSD (sympathicotomy T2–T5) with stellate ganglion sparing and the use of unipolar radiofrequency is feasible, effective, and safe in the setting of untreatable VT.